1992
DOI: 10.1159/000243527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graded Hypoxia on Brain Cell Membrane Injury in Newborn Piglets

Abstract: Alterations in brain cell membrane structure and function during cerebral hypoxia were investigated by measuring Na+, K+-ATPase activity and levels of lipid peroxidation products in brain cell membranes obtained from newborn piglets following exposure to 60 min of hypoxic hypoxia in vivo. Cerebral hypoxia was documented as a decrease in the ratio of phosphocreatine to inorganic phosphate (PCr/Pi) using 31P-NMR spectroscopy. During hypoxia (FiO2 0.07-0.11), PCr/Pi dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 12 publications
2
26
1
Order By: Relevance
“…Na + ,K+-ATPase activity was significantly reduced during cerebra l hypoxia alone (group 3). As in our previous study (20), the magnitude of the decrease in Na+ ,K+-ATPase activity correlated with the magnitude of the decrease in PCr/Pi in each animal. However, in the animals subjected to a hyperglycemic glucose clamp before and during hypoxia, Na+,K+-ATPase activity was preserved at control levels even .. though PCr/p i was reduced, regardless of the magnitude of the change in PCr/Pi.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Na + ,K+-ATPase activity was significantly reduced during cerebra l hypoxia alone (group 3). As in our previous study (20), the magnitude of the decrease in Na+ ,K+-ATPase activity correlated with the magnitude of the decrease in PCr/Pi in each animal. However, in the animals subjected to a hyperglycemic glucose clamp before and during hypoxia, Na+,K+-ATPase activity was preserved at control levels even .. though PCr/p i was reduced, regardless of the magnitude of the change in PCr/Pi.…”
Section: Resultssupporting
confidence: 84%
“…We have shown in the fetus and newborn that cerebral hypoxia leads to alterations in cell membrane structure and function as demonstr ated by increas ed brain cell membrane lipid peroxidation and decreased activity of the cerebral Na+,K+-A'TPase (18)(19)(20). Based on previous studies that demonstrated that hyperglycemia improved surviva l and preserved brain structure in the newborn during hypoxia/ischemia, we hypothesized that hyperglycemia might also act to preserve brain cell membran e structure and function during cerebral hypoxia.…”
mentioning
confidence: 99%
“…16 Because of its similarity in overall shape, gyral pattern, distribution of gray and white matter, and growth pattern to human infants, the piglet brain has been used extensively to model human development. 6,16,17,19,49 The response of the piglet to hypoxia and ischemia appears to parallel that in human infants; cerebral blood flow and metabolism are similar, and the piglet brain matures in a similar manner with respect to myelination and electrical activity. 11,16,40,50 The size of the pig brain is ideally suited for clinically relevant biomechanical modeling of human head trauma, including both focal and inertial injuries involving gray and white matter.…”
Section: Discussionmentioning
confidence: 96%
“…So, we cannot be entirely sure that Na (29,30). The severity of decreases in Na ϩ ,K ϩ -ATPase activity are dependent on decreases in phosphocreatine as has been measured using 31 P-MRS (8). Also, in the present study, the strong correlation between Na ϩ ,K ϩ -ATPase activity and ECBA suggests that electrical stability of the cortical brain cell membrane is directly related to electrical brain activity.…”
Section: Discussionmentioning
confidence: 54%
“…Inasmuch as the transmembrane enzyme Na ϩ ,K ϩ -ATPase is very susceptible to free radical-related lipid peroxidation (7,8), we investigated in the present study whether DFO prevented free radical-induced alterations of the brain cell membrane after global hypoxia and ischemia, simulating severe birth asphyxia, by measuring cortical cell membrane Na ϩ ,K ϩ -ATPase activity in the early reoxygenation and reperfusion phase in newborn lambs. As Na ϩ ,K ϩ -ATPase is important in maintaining membrane potentials, a second objective of this study was to investigate the relation between cortical cell membrane Na ϩ ,K ϩ -ATPase activity and ECBA in the early reperfusion phase using cerebral function monitoring.…”
mentioning
confidence: 99%